The Influence of Market Uncertainty on Sustainable Competitive Advantage with Supply Chain Endurance as a Mediating Variable - Sofiyan, Widya Arif; Khaitu, Thomas Stefanus; Christian , Timotius Febry (International Review of Management and Marketing, 2026)
Market uncertainty poses critical challenges for organizations operating in volatile regulatory environments, yet theoretical understanding of mechanisms linking environmental turbulence to sustainable competitive advantage remains incomplete. This study examines supply chain endurance as a mediating mechanism through which market uncertainty influences competitive advantage within Indonesia’s cigarette industry—a context characterized by intensifying health regulations, supply chain seasonality, and persistent demand volatility. Employing Partial Least Squares Structural Equation Modeling (PLS-SEM) with data from 86 supply chain managers and operational directors, this research tests relationships among market uncertainty, supply chain endurance, and sustainable competitive advantage. Findings reveal that market uncertainty exerts strong positive influence on supply chain endurance (β=0.721, p<0.001), which subsequently contributes to sustainable competitive advantage (β=0.265, p<0.001). Market uncertainty also demonstrates significant direct effects on competitive advantage (β=0.405, p<0.001). Mediation analysis confirms partial mediation (VAF=32.04%), indicating supply chain endurance accounts for approximately one-third of uncertainty’s total effect while substantial direct relationships persist. Results advance dynamic capabilities theory by demonstrating environmental turbulence catalyzes capability development, enrich resource-based view by positioning endurance as VRIN-satisfying strategic resource, and extend contingency theory by revealing environmental characteristics actively shape capability priorities. Practically, findings suggest organizations confronting persistent uncertainty should prioritize endurance investments emphasizing supplier diversification, inventory flexibility, and scenario planning alongside complementary capabilities spanning marketing agility and innovation capacity for comprehensive competitive positioning.